Peran Modal Intelektual Terhadap Kinerja Perusahaan Pada PT Primarindo Asia Infrastructure Tbk Tahun 2008-2017 - Susi Susanti; Catur Martian Fajar; Yunika Komalasari (LPPM Universitas Adhirajasa Reswara Sanjaya, 2020)
ABSTRACT Sales that occurred on PT Primarindo Asia Infrastructure Tbk experienced fluctuations which had an impact on net profit (loss) and company equity. This study aims to examine the effect of intellectual capital consisting of capital employed, human capital, structural capital, relational capital on company performance. The research method used in this research is explanatory method with descriptive descriptive research, and data analysis using research data in the form of financial statements on PT Primarindo Asia Infrastructure Tbk for the period 2008-2017. The novelty in this study is that in previous studies it did not explain which variables were related and their influence was strong or weak and the measurement tools for the performance of the company in previous studies did not use EVA. The results of the correlation analysis show that the relationship of capital employed is very strong in the same direction, strong human capital in the same direction, strong structural capital in the same direction, relational capital is very low negative direction with company performance. The results of partial hypothesis testing can be seen that only capital employed has a significant effect on company performance. Simultaneous hypothesis test results show that there are significant effects between capital employed, human capital, structural capital, relational capital on company performance.